2023
DOI: 10.1136/bcr-2022-253826
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured subclavian artery pseudoaneurysm following a shoulder massage on a background of clavicle non-union

Abstract: We present an unusual case of ruptured subclavian artery pseudoaneurysm following hydrotherapy and shoulder massage session on a background of clavicle non-union.Following a clavicle fracture 16 years ago, which was managed conservatively, a woman in her 30s presents over a decade later with a ruptured subclavian artery pseudoaneurysm.The original midshaft clavicle fracture was sustained 16 years ago. Conservative management was agreed, and she was discharged. Six years ago, she developed a small subclavian ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The initial part of the abnormal subclavian artery was injured during brachial plexus block anesthesia and operation, resulting in the formation and rupture of subclavian artery pseudoaneurysm. Recently, Lawson et al reported a case of chronic subclavian artery pseudoaneurysm due to clavicle nonunion[11]. The patient's pseudoaneurysm ruptured after massage, emergency vascular stent implantation under radiography, and secondary internal xation of clavicular nonunion.…”
mentioning
confidence: 99%
“…The initial part of the abnormal subclavian artery was injured during brachial plexus block anesthesia and operation, resulting in the formation and rupture of subclavian artery pseudoaneurysm. Recently, Lawson et al reported a case of chronic subclavian artery pseudoaneurysm due to clavicle nonunion[11]. The patient's pseudoaneurysm ruptured after massage, emergency vascular stent implantation under radiography, and secondary internal xation of clavicular nonunion.…”
mentioning
confidence: 99%